Isolation and Effect of Al-Tolerant Phosphate Solubilizing Microorganism for Production and Phosphate Absorption of Grasses and Phosphour Dissolution Mechanism - Karti, PDMH; Yahya, S; Sopandie, D; Hardjosuwignyo, S; Yadi, S (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2012)
Abstract. The objective of this research was to study the isolation and effect of Al-tolerant phosphate solubilizing microorganisms to growth, production of grasses and phosphate dissolution mechanism. The planting materials used were S. splendida and C. gayana pols. The treatment consisted of four selected isolates, namely Po = without phosphate solubilizing bacteria(PSB), P1 = RJM.30.2, P2 = FT.3.2, P3 = FT.3.4, P4 = B8016495, P5 = B8016498, P6 = the mixture from four isolates P2-P5. Observed variables were pH, shoot and root dry weight, and P absorption. The best phosphate solubilizing microorganism on acid soil were FP.3.2, FP.3.3, B8016495 and B8016498. Phosphate solubilizing microorganism could not yet increase shoot and root dry weight production on grasses S. splendida and C. gayana, but had shown increasing P shoot and root content and P uptake. On grass S. splendida the best isolate to increase P shoot and root of shoot and root, organic acid. The best phosphate solubilizing microorganism on acid soil content and P uptake was FT.3.3. On grass C gayana the best isolate to increase P shoot and root content and P uptake were RJM.30.2. and FT.3.3. Organic acid exudated by FT.3.3. were oxalic and acetic acid as phosphate dissolution mechanism. Keywords: phosphate solubilizing microorganism, acid soil, forage grasses, Setaria splendida, Chloris gayanaAnimal Production 14(1):13-22, January 2012